Evaluation of Serum and Urine Dickkopf-1 Concentrations and Their Relation with Lipid Profile in Iraqi Women with Breast Carcinoma - Qasim Mahmoud, Hiba; Imran Hamzah, Mohammed; Joudi Ibrahim, Mazin (Malaysian Journal of Science (MJS), 2025)
Invasive ductal carcinomas account for approximately 70%–80% of all breast carcinoma (BC) cases. Dickkopf-1 (DKK-1) is a glycoprotein secreted by the tumour that functions as a negative regulator of Wnt signalling. Various clinical disorders have been linked to the misregulation of Wnt signalling. Several research groups have demonstrated that DKK-1 inhibits the Wnt signalling pathway by forming complexes on the cell surface with low-density lipoprotein receptor-related proteins 5 and 6, rather than directly interacting with Wnt or Frizzled proteins. This project aims to investigate the correlation between serum and urine concentrations of DKK-1 and their relation with lipid profiles in Iraqi women with BC. We compare these findings to those obtained for control and first-degree relative groups and assess whether urine can serve as an alternative to serum for measuring DKK-1 levels. Fasting serum and urine DKK-1 levels, as well as serum lipid profiles, were assessed in 29 patients with BC, 29 first-degree relatives, and 30 age-matched healthy controls. An enzyme-linked immunosorbent assay was employed to measure DKK-1 concentrations in both serum and urine, while the Roche Cobas c111 system was used to analyse urine creatinine and lipid profiles. The concentrations of DKK-1 in urine and serum were significantly higher in patients who BC compared to first-degree relatives and healthy controls (p < 0.01). Total cholesterol and low-density lipoprotein levels in the BC group were elevated compared to the control group, with the first-degree relative group falling in between. Triglyceride and very low-density lipoprotein levels did not show significant differences between the BC and control groups; however, the first-degree relative group had the highest concentrations, which were statistically different from the control group but not from the BC group. high-density lipoprotein concentrations were not significantly different among the three groups (p = 0.093). Receiver operating characteristic curve analysis indicated that the optimal diagnostic thresholds for serum and urine DKK-1 were 196.00 and 270 pg/mL, respectively. These findings suggest that DKK-1 serves as a valuable biomarker for diagnosis and prognosis, as well as a potential treatment option, for BC.